2013
DOI: 10.1121/1.4774276
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of ultrasound propagation in random arrangements of elliptic scatterers: Occurrence of two longitudinal waves

Abstract: Ultrasound propagation in clusters of elliptic (two-dimensional) or ellipsoidal (three-dimensional) scatterers randomly distributed in a fluid is investigated numerically. The essential motivation for the present work is to gain a better understanding of ultrasound propagation in trabecular bone. Bone microstructure exhibits structural anisotropy and multiple wave scattering. Some phenomena remain partially unexplained, such as the propagation of two longitudinal waves. The objective of this study was to shed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…We observed similar results, at least qualitatively, in 2D and in 3D. Four conditions were necessary to observe the two waves in our simple models: The first two points are consistent with previous observations 120 in real cancellous bone [11, chap.11], justifying a posteriori [23]. In the rest of the present article, the simulation of propagation along the main direction in a binary medium made of bone and water with a 50% solid fraction ( Fig.1a) will be referred to as the "reference simulation".…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observed similar results, at least qualitatively, in 2D and in 3D. Four conditions were necessary to observe the two waves in our simple models: The first two points are consistent with previous observations 120 in real cancellous bone [11, chap.11], justifying a posteriori [23]. In the rest of the present article, the simulation of propagation along the main direction in a binary medium made of bone and water with a 50% solid fraction ( Fig.1a) will be referred to as the "reference simulation".…”
Section: Introductionsupporting
confidence: 91%
“…We now move to the case where two compressional waves 329 propagate. Previous work by our group showed that the two 330 waves could be observed in the case of an ultrasound propaga-331 tion along the main direction and for an appropriate range of 332 solid fraction, from 30% to 70% [23] (Fig.1) wave. Fig.4 shows the resulting attenuation coefficients and ve- For all three cases, ultrasound propagation was set perpendicular to the direction of anisotropy so that only one wave could be observed.…”
Section: Two Waves 328mentioning
confidence: 86%
See 1 more Smart Citation
“…Consequently, it is quite difficult the proper interpretation of specific literature-reported studies that did not find a clear diagnostic value for calcaneal QUS devices (24,27). However, further work in this field is ongoing and interesting experimental studies aimed at elucidating the mentioned interaction mechanisms are being continuously published (65)(66)(67)(68)(69)(70). Although the most common QUS devices employ the described through transmission approach to provide parameters such as broadband US attenuation (BUA), speed of sound (SOS) and stiffness index (STI), some recent papers reported the potential of US backscatter as a new approach to osteoporosis diagnosis (34).…”
Section: Qus Approaches For Peripheral Sitesmentioning
confidence: 99%
“…Hosokawa & Otani, 1998). They concluded that the relative motion of the solid-fluid substance is the main reason for the observation of slow wave and this statement was numerically confirmed by Haiat et al (Haïat, Padilla, Peyrin, & Laugier, 2008) and by Meziere et al (Mézière, Muller, Dobigny, Bossy, & Derode, 2013). Nevertheless, one in-vivo experiment has been performed on trabecular bone at the distal end of the radius supporting the observation of the two longitudinal signals (Yamamoto et al, 2009).…”
Section: Biot's Theorymentioning
confidence: 79%